Building Creative Art Product in Jombang Regency by Conserving Mask Puppet - Yanuartuti, Setyo (Harmonia: Journal of Arts Research and Education, 2016)
Building creative industry is one the effort chose to keep up with the ongoing of era development. Traditional art is one of the resource to produce creative art products. Gate Duwur Mask Puppet is a mask performance in Jombang Regency East Java that contains local wisdom. The local wisdom was one of the creativity sources to develop creative art products in Jombang Regency because maintaining Jati Duwur Mask Puppet performance was hard in the middle of the fast society development. The transformation of the source culture (mask puppet) to become the current target culture is one of the efforts made to build creative art. The research on mask dance conservation on mask puppet performance in Jombang was needed. The research method used was an art development through conservation. There were three products of mask dance created as a result of this research. The dances were Gladhen dancers â a couple dance, Mbanmban mask dance â a theatrical group dance, Maduretno-citralanggenan dance â a dance fragment. These mask dance products were a creative realization of a mask performance originated from mask puppet. The community and mask, puppet performer agreed to the development of mask dance to become a more creative art product that could be enjoyed by the young generation.